RADIAL TYRE DEFLECTION OF ROAD VEHICLE IN DEPENDENCE ON TEMPERATURE (Perner's Contacts, 2016)
The paper deals with the tyre deflection of the road vehicle in dependence on the temperature. It also processes the issue of inflating a tyre of road vehicle with nitrogen and whether it has noticeable influence to the magnitude of tyre deflection. The paper evaluates the magnitude of deformation of the tyre in dependence on the different temperatures of the vehicle wheel, which has been heated up to a temperature of 80 °C.